Lenvatinib versus sorafenib for first-line treatment of unresectable hepatocellular carcinoma: patient-reported outcomes from a randomised, open-label, non-inferiority, phase 3 trial. (August 2021) - Vogel, Arndt; Qin, Shukui; Kudo, Masatoshi; Su, Yun; Hudgens, Stacie; Yamashita, Tatsuya; Yoon, Jung-Hwan; Fartoux, Laetitia; Simon, Krzysztof; López, Carlos; Sung, Max; Mody, Kalgi; et al.
Summary: Background: Hepatocellular carcinoma is the third-leading cause of cancer-related death worldwide. Preservation of health-related quality of life (HRQOL) during treatment is an important therapeutic goal. The aim of this study was to evaluate the effect of treatment with lenvatinib versus sorafenib on HRQOL. Methods: REFLECT was a previously published multicentre, randomised, open-label, non-inferiority phase 3 study comparing the efficacy and safety of lenvatinib versus sorafenib as a first-line systemic treatment for unresectable hepatocellular carcinoma. Eligible patients were aged 18 years or older with unresectable hepatocellular carcinoma and one or more measurable target lesion per modified Response Evaluation Criteria in Solid Tumors criteria, Barcelona Clinic Liver Cancer stage B or C categorisation, Child-Pugh class A, Eastern Cooperative Oncology Group (ECOG) performance status of 1 or lower, and adequate organ function. Patients were randomly assigned (1:1) via an interactive voice–web response system; stratification factors for treatment allocation included region; macroscopic portal vein invasion, extrahepatic spread, or both; ECOG performance status; and bodyweight. Patient-reported outcomes (PROs), collected at baseline, on day 1 of each subsequent cycle, and at the end of treatment, were evaluated in post-hoc analyses of secondary and exploratory endpoints in the analysis population, which was the subpopulation of patients with a PRO assessment at baseline. A linear mixed-effects model evaluated change from baseline in PROs, including European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30) and hepatocellular carcinoma-specific QLQ-HCC18 scales (both secondary endpoints of the REFLECT trial). Time-to-definitive-deterioration analyses were done based on established thresholds for minimum differences for worsening in PROs. Responder analyses explored associations between HRQOL and clinical response. This study is registered with ClinicalTrials.gov, NCT01761266 . Findings: Of 954 eligible patients randomly assigned to lenvatinib (n=478) or sorafenib (n=476) between March 14, 2013, and July 30, 2015, 931 patients (n=468 for lenvatinib; n=463 for sorafenib) were included in this analysis. Baseline PRO scores reflected impaired HRQOL and functioning and considerable symptom burden relative to full HRQOL. Differences in overall mean change from baseline estimates in most PRO scales generally favoured the lenvatinib over the sorafenib group, although the differences were not nominally statistically or clinically significant. Patients treated with lenvatinib experienced nominally statistically significant delays in definitive, meaningful deterioration on the QLQ-C30 fatigue (hazard ratio [HR] 0·83, 95% CI 0·69–0·99), pain (0·80, 0·66–0·96), and diarrhoea (0·52, 0·42–0·65) domains versus patients treated with sorafenib. Significant differences in time to definitive deterioration were not observed for other QLQ-C30 domains, and there was no difference in time to definitive deterioration on the global health status/QOL score (0·89, 0·73–1·09). For most PRO scales, differences in overall mean change from baseline estimates favoured responders versus non-responders. Across all scales, HRs for time to definitive deterioration were in favour of responders; median time to definitive deterioration for responders exceeded those for non-responders by a range of 4·8 to 14·6 months. Interpretation: HRQOL for patients undergoing treatment for unresectable hepatocellular carcinoma is an important therapeutic consideration. The evidence of HRQOL benefits in clinically relevant domains support the use of lenvatinib compared with sorafenib to delay functional deterioration in advanced hepatocellular carcinoma. Funding: Eisai and Merck Sharp & Dohme.